LABORATORY MODELS FOR STUDYING THE HEALTH EFFECTS OF AIR POLLUTION AND CLIMATE CHANGE - Mohammed Hadi Aidrous Madkhali, Yahia Moaber Ali Faoug, Fawziah Ahmed Abdullah Awaji, Kholoud Bahlool Alameer, Eissa Moussa ahmed Tawashi, Anwar Abdu Abdullah Refaei, Mohammed Yahya M Almashuri, Dael Ahmed Mohammed Shajiri, Fatimah Ahmed Ali Hzazi; Nesren hmoud Zeeid hothan, ‏Nassrin Abdulrahman Abdullah Almugren, Thuraya Mahmoud Hassan Alhindi, Khalid Khalil Ghalfan Kamili, Mada Hammoud Zaid Hothan, Ebtesam Khaled Alhadi (Chelonian Research Foundation, 2022)
The subject of soil microbiology has now entered the age of big data. However, there are still obstacles in connecting laboratory, field, and model-based investigations of ecosystem functioning. The limiting of variables in laboratory tests fails to include the interactions of many environmental forces in their natural settings. This often leads to conflicting results between laboratory and field investigations, which may potentially mislead the creation and predictions of models. Transferring soil microbiology research from the lab to ecosystems is a significant issue for environmental scientists. However, it has the potential to provide valuable information to policymakers in order to create climate-smart and resource-efficient ecosystems. The process of upscaling involves not just scaling up, but also the need to separate and understand the functional links and activities at each level. There are three possible explanations for the differences between studies conducted in laboratories and those conducted in the field. These explanations include the dynamics of space and time, disturbances in sampling, and the interactions between plants, soil, and microbes. Additionally, there are three important considerations to keep in mind when connecting observations with model predictions. These considerations include the effects that occur across different scales, the complex relationships between different processes, and the regulation of multiple factors. Field-based research is only able to investigate a restricted range of environmental variation. To fully understand the underlying processes, it is necessary to complement these investigations with laboratory and mesocosm manipulation experiments. The lack of information in scaling up soil microbiology from laboratory to ecosystems should encourage multidisciplinary cooperation including experimental, observational, theoretical, and modeling research. Keywords: Laboratory, ecosystem, soil microbiology, review.